Reconstruction of National Land Law Based on Social Justice and Agrarian Reform - Lubis, Ikhsan; Lubis, Duma Indah Sari; Lubis, Andi Hakim (Marcapada: Jurnal Kebijakan Pertanahan, 2025)
This study aims to analyze and reconstruct the national land law system in Indonesia based on the principles of social justice and the social function of land. The main focus of this research is to identify challenges in the implementation of social justice principles, including agrarian conflicts, legal uncertainty, and the marginalization of indigenous communities. The methodology employed is normative legal research, with data collection entailing the examination of secondary documents pertinent to the execution of the Basic Agrarian Law (UUPA). The results of the study indicate that the reconstruction of the land law system based on social justice and the social function of land can improve community access to land resources, reduce conflict, and encourage sustainable development. These findings also suggest the need for policy reform and more effective law enforcement to address social dynamics on the ground. Policymakers can expect this research to provide recommendations for the formulation of regulations that are fairer and more responsive to community needs.